Development of STEAM-based Teaching Materials using Google Sites to Improve HOTS of Fifth Grade Elementary School Students - Novia Rita; Yanti Fitria; Syafri Ahmad; Melva Zainil (Sakura Digital Nusantara, 2026)
Purpose: In response to the low ability of Higher Order Thinking Skills (HOTS) caused by teacher-centered learning and the lack of digital teaching materials that support analytical, evaluative, and creative thinking processes, this study aims to develop Science, Technology, Engineering, Arts, and Mathematics (STEAM) based teaching materials using Google Sites to improve the HOTS abilities of fifth grade elementary school students. Methods: This study used the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study was conducted at SDN 26 Kayu Pasak, Padang City, West Sumatra, with 21 fifth-grade students and their homeroom teachers as subjects. Data collection techniques were carried out through observation, interviews, questionnaires, and tests. Data analysis used expert validity tests, practicality tests, and effectiveness tests using N-Gain. Findings: Based on the research results, the STEAM-based learning materials created were very practical with a student response rate of 97% and a teacher response rate of 95%, included in the very valid category with a score above 90%, and successfully improved high-level thinking skills with an N-Gain value of 0.84 (high category). Research Implications: This study shows how STEAM-based teaching resources can be utilized as a substitute for creative learning to enhance students' HOTS and improve teaching standards in elementary schools. Originality: This study focuses on the creation of STEAM teaching resources that are specifically designed and proven to have an impact on improving the higher-order thinking skills of fifth-grade elementary school students through a systematic, reliable, useful, and successful methodology.